Reconstruction of Proximal Humerus Using Custom Made Acrylic Prosthesis in Malignant Bone Tumors - Singh, Kumar Amerendra (J Orthop Case Rep, 2016)
INTRODUCTION: Proximal humerus is a common site for malignant bone tumors. The mainstay of treatment involves radical excision and reconstruction. Reconstructing the proximal humerus is quite challenging. The best modality of treatment is a modular endoprosthesis which is expensive. Here, we present two cases where the proximal humerus was reconstructed with acrylic prosthesis. CASE REPORT: A 19-year-old male and 51-year-old lady from India presented with painful swellings of the upper arm with a clinical diagnosis of Ewing’s sarcoma arising from the left humerus and secondary metastatic tumor of proximal end of right humerus, respectively. They were treated with radical excision of tumor, and the upper two-third of the humerus were reconstructed using custom made acrylic endoprostheses. CONCLUSION: Reconstruction of proximal humeral defect with custom made acrylic prosthesis is less expensive and an effective alternative to modular endoprosthesis, which can be used in developing countries.